Improvement in severe lower respiratory symptoms and small airway function in World Trade Center dust exposed community members. Issue 9 (September 2016) - Caplan‐Shaw, Caralee; Kazeros, Angeliki; Pradhan, Deepak; Berger, Kenneth; Goldring, Roberta; Zhao, Sibo; Liu, Mengling; Shao, Yongzhao; Fernandez‐Beros, Maria Elena; Marmor, Michael; Levy‐Carrick, Nomi; Rosen, Rebecca; et al.
Abstract : Objective: Longitudinal assessment of lower respiratory symptoms (LRS) in community members with World Trade Center (WTC) exposures. Methods: Adult members of a treatment program with complete standardized visits were evaluated (n = 798). Association of demographic characteristics, mental health symptoms and lung function with trajectory of LRS between initial and monitoring visit was evaluated. Results: Severe LRS were present in 70% at initial and 63% at monitoring visit. Initial severe LRS were associated with WTC dust cloud exposure and mental health symptoms. Spirometry measures were not associated with LRS severity or trajectory; improvement in LRS was associated with improved lung function measured with forced oscillometry techniques. Conclusion: Many community patients in a WTC treatment program had severe LRS associated with exposures and mental health symptoms. Improvement in LRS was associated with improvement in measures of small airway function. Am. J. Ind. Med. 59:777–787, 2016. © 2016 Wiley Periodicals, Inc.